THE USE OF AGRICULTURE 4.O - Brusadin, Isabely Edvirges; Alves, Marcos Rafael; Cavichioli, Fabio Alexandre (Revista Interface Tecnológica, 2023)
Agriculture 4.0 represents a set of digital technologies through software, systems and equipment. It allows the optimization of agricultural production in all stages, from planting to harvesting. Together, these tools help to the maximum in management and production, as well as advancing all the time along with new research. To improve more and more and reduce the waste that the producer or the factory among others may have, in addition to presenting a potential to avoid degradation of the environment. This article aims to present Agriculture 4.0 and some of its technologies and systems, references used in the field. The objective of this article is to describe technologies and analyze whether they provide benefits to the rural producer. The methodology adopted for this project was bibliographic that used articles, books and websites focused on the proposed theme, whose purpose is to give the reader a basis on available works that relate to the project. With this, the research points out that there is an increase in productivity that agriculture 4.0 and the technologies addressed provide savings, precision and reduction of impact to the environment for the rural producer in carrying out their agricultural activities ranging from soil preparation and nutrition, planting and care of the crop, to the harvest,  Through the adoption of state-of-the-art machinery and equipment within the property, where Agriculture 4.0 has sophisticated features such as autopilot, global positioning system, telemetry and currently the novelty that are autonomous tractors.
Keywords: digital agriculture; global positioning system; technology in agribusiness